2015
DOI: 10.1016/j.procir.2015.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Model for Prediction of Cutting Forces in Turning of Non-axisymmetric Parts

Abstract: Most of the existing mechanistic (semiempirical) models for turning are orientated towards continuous cut and are applicable neither to nonaxisymmetric parts, nor to the particular case of interrupted turning, so common in real workpieces. Some commercial software packages which simulate machining process by FEM enable to calculate interrupted cut. However, their high computational cost limits the simulations to a very short length of cut, hardly completing one cutting revolution. By contrast, mechanistic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…However, reducing cutting edge angle also leads to the rise of temperatures and to excessively thin chips that accelerate tool wear. Cascón et al [8] proposed a force prediction model from CAM simulations along the machining path of non-symmetric parts. In order to mitigate the effects of intermittent hitting, the possibility of reducing cutting edge angle was explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, reducing cutting edge angle also leads to the rise of temperatures and to excessively thin chips that accelerate tool wear. Cascón et al [8] proposed a force prediction model from CAM simulations along the machining path of non-symmetric parts. In order to mitigate the effects of intermittent hitting, the possibility of reducing cutting edge angle was explored.…”
Section: Introductionmentioning
confidence: 99%
“…From that figure, it can be observed that the cutting force has higher values than passive and feed forces, and both of the torque and the power have a periodic nature. That is due to lead angle effect which is considered as a determinant factor in interrupted turning due to the intermittent hitting [73]. Figure 5 plotted the effect of different investigated factors (coating condition, nose radius, cutting speed, feed rate, and cutting depth) on the resultant force as well as the force components.…”
Section: Cutting Forcesmentioning
confidence: 99%
“…Numerous developments in numerical methods and simulations associated with the existence of increasingly powerful computers make it possible to study tool wear using FEM. Modeling issues are addressed by considering microstructures as homogeneous characteristics and corresponding verification methods [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%